Religion and Social Conflict - Robert Lee 1929-; Martin E. Marty 1928- (New York Oxford University Press, 1964)
Based upon Lectures Given at The Institute of Ethics and Society at San Francisco Theological Seminary
Keywords: Pastoral Theology (3GddGghJ GdQYhjs; Christianity and politics; Social conflict -- United States